Analyzing Atonal Music : Pitch-Class Set Theory and Its Contexts - Schuijer, Michiel (Book collections on Project MUSE., 2008)
"For the past forty years, pitch-class set theory has served as a frame of reference for the study of atonal music, through the efforts of Allen Forte, Milton Babbitt, and others. It has also been the subject of sometimes furious debates between music theorists and historically oriented musicologists, debates that only helped heighten its profile." "Analyzing Atonal Music: Pitch-Class Set Theory and Its Contexts combines thorough discussions of musical concepts with an engaging historical narrative. Pitch-class theory is treated here as part of the musical and cultural landscape of the United States. The theory's remarkable rise to authority is related to the impact of the computer on the study of music in the 1960s, and to the American university in its double role as protector of high culture and provider of mass education."--Jacket